2018
DOI: 10.1021/acs.jafc.8b05140
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Six Typical Processing Methods on the Chemical Composition of Tea Leaves Using a Single Camellia sinensis Cultivar, Longjing 43

Abstract: While the Camellia sinensis cultivar and processing method are key factors that affect tea flavor and aroma, the chemical changes in nonvolatile components associated with the tea processing method using a single cultivar of C. sinensis have not been reported. Fresh leaves from C. sinensis Longjing 43 were subjected to six tea processing methods and evaluated by targeted and untargeted chromatographic procedures. On the basis of targeted assessment of the total catechin content, three clusters were identified:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(128 citation statements)
references
References 40 publications
(61 reference statements)
3
110
0
Order By: Relevance
“…Table 5 shows the antioxidant activities of the tested samples (ethyl acetate, butanol and aqueous fractions), which were high in both s/h ratio conditions, indicating that the activity it is not affected by the vessel geometry or the fermented volume. The enhancement of antioxidant activity has been reported in others studies [26,27], which can be due to the interactions between microbial enzymes and phytochemicals in the fermented media. In the case of the two tested ratios, the increase in the phenolic content as well as in the antioxidant activity were higher with the highest vessel ratio, increasing from 70.9% inhibition in the nonfermented tea to 96.2% in the butanol extracts and from 14.6 to 23.5% in the water extracts.…”
Section: Phenolic Composition and Antioxidant Activitysupporting
confidence: 52%
See 1 more Smart Citation
“…Table 5 shows the antioxidant activities of the tested samples (ethyl acetate, butanol and aqueous fractions), which were high in both s/h ratio conditions, indicating that the activity it is not affected by the vessel geometry or the fermented volume. The enhancement of antioxidant activity has been reported in others studies [26,27], which can be due to the interactions between microbial enzymes and phytochemicals in the fermented media. In the case of the two tested ratios, the increase in the phenolic content as well as in the antioxidant activity were higher with the highest vessel ratio, increasing from 70.9% inhibition in the nonfermented tea to 96.2% in the butanol extracts and from 14.6 to 23.5% in the water extracts.…”
Section: Phenolic Composition and Antioxidant Activitysupporting
confidence: 52%
“…Black tea contains several phenolic compounds that may be subjected to biotransformation during processing, increasing or reducing their concentration. Yeast and bacteria are also known to play a crucial role in the metabolism of these compounds [27]. For the identified compounds, TB and CAA were completely consumed, and CAFF was nearly depleted decreasing from a concentration of 35142.4 to 41.1 mg/kg after 21 days of fermentation.…”
Section: Identification and Quantification Of The Main Phenolic Compomentioning
confidence: 99%
“…Wang et al [252] tracked the metabolite profiles of an identical batch of fresh leaves that was processed into each of the six major tea types, and the results may provide insight as to the relative capacities of certain tea types to confer anti-depressive effects through different mechanisms [252]. This study found significant differences in the profiles of certain metabolites with considerable relevance to the antidepressant mechanisms discussed in this review.…”
Section: Discussionmentioning
confidence: 82%
“…For the initial analysis of the taste and aroma, the FL, IW, and SW samples were freeze-dried for 24 h before undergoing a sensory evaluation as previously described (Wang et al, 2019c). Water, Total Polyphenol, Total Flavonoid, Catechin, Lignin, Volatile Compound, Jasmonic Acid, and Methyl Jasmonate Contents In order to determine the related metabolites, three independent biological replicates for the above-mentioned samples (FL, IW, and SW) were used for following studies.…”
Section: Plant Materials Sample Preparation and Sensory Analysesmentioning
confidence: 99%